The Impact of Organizational Culture on Job Satisfaction and Employee Retention in Multinational Companies - Junaidi, Junaidi; Kusuma, Emeralda Ayu; Pramono, Danan Wuryanto (Universitas Syiah Kuala, 2025)
This qualitative literature study explores the impact of organizational culture on job satisfaction and employee retention within multinational companies (MNCs). Drawing upon a comprehensive review of peer-reviewed scholarly sources, this research identifies how distinct cultural values, leadership styles, communication practices, and corporate philosophies shape the work environment and influence employee experiences. The study highlights that a strong, adaptive, and inclusive organizational culture significantly contributes to enhanced job satisfaction by aligning employee values with organizational goals, fostering trust, and promoting a sense of belonging. Additionally, such cultural environments are linked to higher retention rates, as employees are more likely to remain with organizations that support personal growth, cross-cultural collaboration, and transparent leadership. The findings of this literature-based inquiry emphasize the strategic importance of cultural alignment in talent management, particularly in the context of global operations where cultural diversity presents both challenges and opportunities. This study provides theoretical insights for scholars and practical implications for human resource professionals in formulating culture-driven retention strategies.